Parameters and design optimization of the ring piezoelectric ceramic transformer - Jiří Erhart (Journal of Advanced Dielectrics, 2015)
Main aim of the presented paper is the theoretical analysis and experimental verification of the transformation parameters for the new type of nonhomogeneously poled ring transformer. The input part is poled in the thickness direction and output part in the radial direction. Two transformer geometries are studied — the input part is at inner ring segment, or it is at the outer ring segment. The optimum electrode size aspect ratios have been found experimentally as d1∕D≈0.60−0.65 for the ring with aspect ratio d∕D=0.2. The fundamental as well as higher overtone resonances were studied for the transformation ratio, the optimum resistive load, efficiency and no-load transformation ratio. Higher overtones have better transformation parameters compared to the fundamental resonance. The new type ring transformer exhibits very high transformation ratios up to 200 under no-load and up to 13.4 under a high efficiency of 97% at the optimum load conditions of 10 kΩ. Strong electric field gradient at the output circuit is applicable for the electrical discharge generation.